2019
DOI: 10.1002/ijc.32040
|View full text |Cite
|
Sign up to set email alerts
|

RET, a targetable driver of pancreatic adenocarcinoma

Abstract: Pancreatic ductal adenocarcinoma (PDA) remains a deadly disease, affecting about 40,000 individuals in the United States annually. We aimed to characterize the role of RET as a co‐driver of pancreas tumorigenesis. To assess the role of RET as a co‐driver of PDA, we generated a novel triple mutant transgenic mouse based on the cre‐activated p53R172H gene and a constitutively active RET M919T mutant (PRC). Survival analysis was performed using Kaplan–Meier analysis. Study of human PDA specimens and Pdx‐1‐Cre/Kra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…RET is altered and potentially actionable in other solid tumor types, albeit at low frequencies. RET alterations occur in ~1.9% of pancreatic cancers ( 41 ) whereas wild-type RET, co-receptor GFRα1, and GDNF are overexpressed in 50-70% of pancreatic cancer cases ( 194 , 195 ). Additionally, Ceyhan and colleagues demonstrated that RET activation by another GFL, Artemin, can promote invasion and migration of pancreatic cancer cells ( 196 ).…”
Section: Aberrant Ret Signaling In Tumorigenesismentioning
confidence: 99%
“…RET is altered and potentially actionable in other solid tumor types, albeit at low frequencies. RET alterations occur in ~1.9% of pancreatic cancers ( 41 ) whereas wild-type RET, co-receptor GFRα1, and GDNF are overexpressed in 50-70% of pancreatic cancer cases ( 194 , 195 ). Additionally, Ceyhan and colleagues demonstrated that RET activation by another GFL, Artemin, can promote invasion and migration of pancreatic cancer cells ( 196 ).…”
Section: Aberrant Ret Signaling In Tumorigenesismentioning
confidence: 99%
“…RET activation in cancers through RET fusions or mutations. ,, CML, chronic myeloid leukemia; NSCLC, non-small cell lung cancer; PTC, papillary thyroid cancer; MTC, medullary thyroid cancer.…”
Section: Ret Implications In Cancermentioning
confidence: 99%
“…Nerve growth factor (NGF) has been considered the most potent pain inducer across multiple cancer models and currently holds the most promise for management of pain associated with cancer initiation and progression. Inhibition of NGF binding to the receptor TrkA in preclinical models strongly reduced mechanical, thermal and spontaneous facets of cancer-induced bone pain ( Halvorson et al, 2005b ; Jimenez-Andrade et al, 2011 ; Buehlmann et al, 2019 ), pancreatic cancer pain ( Stopczynski et al, 2014 ; Amit et al, 2019 ), and oral cancer pain ( Ye et al, 2011 ). A phase II clinical trial using anti-NGF antibody, fulranumab, as adjunctive therapy for cancer-related pain found no significant effect on pain intensity via visual analog scale; however, significant improvement on the Brief Pain Inventory subscales suggested improved quality of life ( Slatkin et al, 2019 ).…”
Section: Animal Models Of Cancer-related Painmentioning
confidence: 99%